Student Learning Outcomes in Mathematics Through Problem-Based Learning: Hasil Belajar Matematika Siswa Melalui Problem-Based Learning - Roki Ramadhani; Randi Eka Putra; Elvima Nofrianni (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The persistent challenge in elementary mathematics lies in students’ low achievement, often caused by monotonous instruction and limited engagement strategies. Specific Background: At SDIT Andalusia, Grade V students demonstrated low completion rates, highlighting the urgency of adopting more student-centered methods. Knowledge Gap: Previous studies affirm the promise of Problem-Based Learning (PBL), but limited evidence exists on its contextual use in elementary mathematics with real-life integration. Aims: This study examined whether PBL can improve both the learning process and outcomes in Grade V mathematics. Results: Conducted through Classroom Action Research with two cycles, findings showed a rise in mastery from 55.55% in the first cycle to 92.59% in the second cycle. Average student scores increased from 69.33 to 80.48. Novelty: Unlike typical PBL applications, this research embedded local daily-life problems, fostering relevance and stronger engagement. Implications: Results suggest that contextualized PBL supports active participation, conceptual understanding, and higher achievement, offering an adaptable strategy for elementary mathematics instruction. Highlight Improved student outcomes from 55.55% to 92.59% mastery Active participation and engagement increased through contextual PBL Real-life integration made mathematics learning more meaningful Keyword Problem Based Learning, Mathematics Learning, Student Outcomes, Classroom Action Research, Elementary Education